O ESPORTE NA ESCOLA: OS SABERES E CONHECIMENTOS DOCENTES NAS AULAS DE EDUCAÇÃO FÍSICA DOS ANOS FINAIS DO ENSINO FUNDAMENTAL - Leifeld, Fabiana (2016)
This work has as object of study the knowledge and teaching skills of Physical Education teachers to thematize the sport in Physical Education from the final years of elementary school. The research is characterized as qualitative. The central question of research that seeks to answer is: What are the knowledge and teaching skills of Physical Education teachers to thematize the sport in Physical Education from the final years of elementary school? The research objectives are: a) Identify the knowledge and teaching skills of Physical Education teachers to thematize the sport in Physical Education from the final years of primary education; b) To analyze the knowledge and teaching skills used by the teacher to thematize the sport in Physical Education from the final years of primary education c) Check the origin of students' knowledge about the sport. The theoretical basis of the research was substantiated by related studies: the school sports (BRACHT, 2005; KUNZ, 2000a, 2000b; BETTI, 1995, 1999, 2009; FREIRE, 1989; COLETIVO DE AUTORES, 1992; NEIRA, 2009, 2014); the concepts related to sports as a phenomenon sociocultural (TUBINO, 2006, 2010); issues related to pedagogy of school sport (REVERDITO; SCAGLIA, 2009; PAES; BALBINO, 2014; SADI, 2010; TANI; BENTO; PETERSEN, 2006); the teacher knowledge and teaching knowledge (TARDIF, 2009, 2014; GAUTHIER et al., 2006 SHULMAN, 2005; BORGES, 2004); the assumptions on Brazilian education (SAVIANI, 2008); and the concepts of habitus and field (BOURDIEU, 1983a, 1983b, 2013; NOGUEIRA, NOGUEIRA, 2009). The methodological routing work was foundation studies Flick (2004), Sampieri et al. (2013), Gil (2008) and Bardin (2011). The survey was conducted in three (3) schools from public schools in the city of Carambeí/PR, with the subject three (3) Physical Education teachers, sixty-eight (68) students from 8 years and seventy-two (72) students in the 9th grade of elementary school, totaling one hundred forty-three (143) subjects participating of the research. As research instruments the research were used observation, interview and questionnaire. The survey data were organized and analyzed in accordance with the assumptions of Content Analysis (BARDIN, 2011). The survey results indicate that the Physical Education teacher has knowledge and expertise in the area, which are made throughout his career as well as his subjectivity, both of which contribute to the theming of the sport in Physical Education classes the final years of elementary school.